2019
DOI: 10.1021/acs.langmuir.9b01362
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Equilibrium Droplet Shapes on Chemically Striped Patterned Surfaces Using Phase-Field Method

Abstract: We systematically investigate the equilibrium shapes of droplets deposited on a set of chemically striped patterned surfaces by using an Allen–Cahn-type phase-field model. Varying the widths of the stripes d, the volume V, as well as the initial positions of the droplets, we release the droplets on the top of the surfaces and observe the final droplet shapes. It is found that there are either one or two equilibrium shapes for a fixed ratio of d/V 1/3 and each equilibrium shape corresponds to an energy minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 73 publications
1
35
0
Order By: Relevance
“…wherein using p f (m) as the liquid-gas interface thickness, we can identify 1 2 p f 2 | ∇φ | 2 as the interfacial free-energy density and K 0 = λ 4 p f 2 (φ 2 − 1) 2 [37] is the bulk-energy density. To choose the interface thickness p f we referred to Wu et al [38]. They observed that the numerical results vary drastically for Cahn number Cn = p f d 0 > 0.15.…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…wherein using p f (m) as the liquid-gas interface thickness, we can identify 1 2 p f 2 | ∇φ | 2 as the interfacial free-energy density and K 0 = λ 4 p f 2 (φ 2 − 1) 2 [37] is the bulk-energy density. To choose the interface thickness p f we referred to Wu et al [38]. They observed that the numerical results vary drastically for Cahn number Cn = p f d 0 > 0.15.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…If we consider a realistic value (thickness on the nm scale) of the interface then the number of grid cells becomes so large that it requires a supercomputer to simulate. Thus, for numerical modeling of such sharp interfaces, researchers use the maximum feasible value of the interface thickness, which generally ranges from 10 to 100 μm [38]. The mixing energy density λ (N) is related to the interfacial energy of the droplet σ as σ = 2 √ 2 3 λ p f [36].…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Approaches that explicitly model non-equilibrium at the contact line by a time-dependent (relaxation) boundary condition at the solid surface [53,64,65], as used e.g. in the computations in [66], are not considered here.…”
Section:   mentioning
confidence: 99%
“…Different from wetting on homogeneous surfaces, the droplet morphology will adapt to the alternations of wettability on the chemically heterogeneous surface, and the droplet's final shape strongly depends on the topology of wettability of the surface. Various chemically heterogeneous surfaces such as stripes [8][9][10] , square 11,12 , and triangular patterns 13 have been investigated. Striped surfaces get a lot of attention due to their relatively easy fabrication.…”
Section: Introductionmentioning
confidence: 99%